Review of Change Detection Techniques for Remotely Sensed Images - Sharma, Abhishek; Gulati, Tarun (International Journal of Computer Sciences and Engineering, 2025)
The use of remotely sensed image has been a wide area in research. Different images of the same scene captured by the satellites at different times can provide information about the significant changes that held on earth with time. Many techniques for change detection has been developed while new techniques are also emerging. This paper gives a review of pixel based and transformation based techniques used for change detection. The paper begins with the discussion on pixel based techniques like image differencing, Image Ratioing and Image regression. Then, transformation based techniques like principal component analysis and change vector analysis has been discussed in detail. The paper has been concluded with the comparison of the discussed techniques based on advantages, limitations and applications.